2022
DOI: 10.1542/peds.2021-055570
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and At-Risk Rates for Pediatric Asthma Morbidity

Abstract: BACKGROUND AND OBJECTIVES Compared with population-based rates, at-risk rates (ARRs) account for underlying variations of asthma prevalence. When applied with geospatial analysis, ARRs may facilitate more accurate evaluations of the contribution of place-based social determinants of health (SDOH) to pediatric asthma morbidity. Our objectives were to calculate ARRs for pediatric asthma-related emergency department (ED) encounters and hospitalizations by census-tract in Washington, the District… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Analyses that favour at-risk rates over populationrisk rates also provide greater insight into the social determinants of health that drive disparities, so that targeted interventions can be developed to promote equity in health outcomes [45]. This is the importance of accurate prevalence information: we cannot appropriately study or address disparities without a clear understanding of who is at the greatest risk.…”
Section: The Importance Of Reliable Prevalence Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses that favour at-risk rates over populationrisk rates also provide greater insight into the social determinants of health that drive disparities, so that targeted interventions can be developed to promote equity in health outcomes [45]. This is the importance of accurate prevalence information: we cannot appropriately study or address disparities without a clear understanding of who is at the greatest risk.…”
Section: The Importance Of Reliable Prevalence Datamentioning
confidence: 99%
“…Children from historically marginalized groups, including those with non-Hispanic Black or Puerto Rican ancestry, are more likely to develop asthma [ 1 ]. Differences in asthma prevalence rates between sub-groups of the larger U.S. population are informed by structural racism and inequities in American society [ 44 ▪▪ ], factors which also contribute to morbidity and confound analyses that rely on census-based population data [ 45 ]. When outcomes comparisons are limited to children who are at-risk for asthma morbidity (based on NHIS prevalence data), a different picture emerges, and indicates that disparities for black children may be improving [ 1 ].…”
Section: The Importance Of Reliable Prevalence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the racist public policies and practices implemented almost 100 years ago continue to create areas of social vulnerability, limited opportunity, and poor health outcomes. Several studies have further explored the structural and social risks associated with adverse asthma outcomes [53,54 ▪▪ ,55 ▪▪ ,56]. Experiencing discrimination, along with markers of poverty, exposure to violent crime, and caregiver educational attainment, are all associated with increased healthcare utilization for children with asthma.…”
Section: Systemic Racism and Asthma Riskmentioning
confidence: 99%
“…A longitudinal analysis of 544 children in the Chicago Initiative to Raise Asthma Health Equity found that health literacy and education were important mediators of racial and ethnic disparities in asthma [15]. Another study of 4321 children in the D.C. Pediatric Asthma Registry found that decreased educational attainment and violent crime were the social determinants of health most significantly associated with risk of asthma emergency department visits and hospitalizations [16]. These findings must be considered when implementing community education and warning systems.…”
Section: Race and Social Determinants Of Healthmentioning
confidence: 99%